The perpetual trouble with network products: Why IT firms choose partial compatibility - Manfred Stadler; Céline Tobler Trexler; Maximiliane Unsorg (University of Tübingen, Faculty of Economics and Social Sciences, 2021)
Compatibility of network products is an important issue in markets for communication technology as well as hard- and software products. Empirical findings suggest that firms competing in these markets typically choose intermediate degrees of product compatibility. We present a strategic two-stage game of two firms deciding strategically or commonly on the degree of product compatibility in the first stage and on prices in the second stage. Indeed, partial compatibility constitutes a subgame perfect Nash equilibrium when coordination costs of standardization are high and the installed bases are low.
urn:nbn:de:bsz:21-dspace-1178581; hdl:10900/117858
Keywords: C72; L13; L15; 330; Compatibility; Network Products; Network Effects